Supporting migration as a response to climate risk: precarity, adaptive capacity, and well-being dimensions - Mark G L Tebboth; Reetika R Subramanian; Nitya Rao; W Neil Adger; Chandni Singh; Amina Maharjan; Tasneem Siddiqui (Current Opinion in Environmental Sustainability, 2026)

Relative importance of climate versus socio-environmental development changes to 2050 in rural coastal Bangladesh—a system analysis - Attila N. Lázár; Robert J. Nicholls; Craig W. Hutton; Andres Payo; Helen Adams; Anisul Haque; Derek Clarke; Mashfiqus Salehin; Alistair Hunt; Andrew Allan; W. Neil Adger; M. Munsur Rahman; et al. (Regional Environmental Change, 2026)
Climate change and development are having a profound influence on the integrity of coastal Bangladesh’s people, economy and ecology with climate change widely considered the dominant driver. Our bespoke integrated assessment model (IAM) simulates these changes for rural areas by coupling physical models with economic models, considering shocks like cyclone landfalls, and utilising substantial primary/secondary datasets and stakeholder-derived future scenarios. As such, this study assesses the Bangladesh coastal system’s sensitivity to climate change and policy decisions to 2050. The IAM results suggest that flooding and salinisation have high sensitivity to climatic and environmental drivers, and agricultural productivity is strongly dependent on farming methods and investment in better crop varieties to counteract these changes. Inequality, poverty and GDP per capita are more sensitive to non-climatic drivers. Nonetheless, extreme climatic conditions do impact livelihoods due to economic damage with variable effects across different household types. At least over the next 25 years, development choices (i.e. concrete adaptation actions) will have a similar if not stronger influence on livelihoods and economic wellbeing in rural coastal Bangladesh than climate-driven environmental change. This IAM approach supports decision makers to identify sustainable development pathways that address both current socio-environmental vulnerability as well as develop a more climate-resilient future.

Habitability for a connected, unequal and changing world - Harald Sterly; Marion Borderon; Patrick Sakdapolrak; Neil Adger; Ayansina Ayanlade; Alassane Bah; Julia Blocher; Suzy Blondin; Sidy Boly; Timothée Brochier; Loïc Brüning; Simon Bunchuay-Peth; et al. (Global Environmental Change, 2025)

Improving the effectiveness of climate change adaptation measures - Daniel Puig; Neil W. Adger; Jon Barnett; Lisa Vanhala; Emily Boyd (Climatic Change, 2025)
To a large degree, economic metrics and mechanisms underpin the design of adaptation policies. Such a focus has undesired consequences on the effectiveness of adaptation measures as well as on our ability to prevent incommensurable losses. The article puts forward four strategic changes in adaptation policy that shift the focus away from markets and toward community-level visions of what a liveable future entails. These changes involve accommodating diverse ethical positions, through decision-making processes that are rich in information, include diverse perspectives, and are transparent with respect to the value trade-offs they entail; reflecting social norms in adaptation, through community-led initiatives whereby local priorities and cultural expressions are given centre-stage in the design of adaptation responses; limiting path dependence, through champions within key institutions that are prepared to affect change in times of disruptive climate disasters; and enfranchising marginalised groups, notably by incorporating multiple knowledges and worldviews in adaptation policy, promoting deliberation and negotiation, and subverting exclusionary practices.

Migrants as sustainability actors: Contrasting nation, city and migrant discourses and actions - Claudia Fry; Emily Boyd; Mark Connaughton; W. Neil Adger; Maria Franco Gavonel; Caroline Zickgraf; Sonja Fransen; Dominique Jolivet; Anita H. Fábos; Ed Carr (Global Environmental Change, 2024)

Micro-scale transformations in sustainability practices: Insights from new migrant populations in growing urban settlements - Mumuni Abu; Samuel N.A. Codjoe; W. Neil Adger; Sonja Fransen; Dominique Jolivet; Ricardo Safra De Campos; Maria Franco Gavonel; Charles Agyei-Asabere; Anita H. Fábos; Caroline Zickgraf (Global Environmental Change, 2024)

Health and wellbeing implications of adaptation to flood risk - Tara Quinn; Stacey Heath; W. Neil Adger; Mumuni Abu; Catherine Butler; Samuel Nii Ardey Codjoe; Csaba Horvath; Pablo Martinez-Juarez; Karyn Morrissey; Conor Murphy; Richard Smith (Ambio, 2023)
Adaptation strategies to ameliorate the impacts of climate change are increasing in scale and scope around the world, with interventions becoming a part of daily life for many people. Though the implications of climate impacts for health and wellbeing are well documented, to date, adaptations are largely evaluated by financial cost and their effectiveness in reducing risk. Looking across different forms of adaptation to floods, we use existing literature to develop a typology of key domains of impact arising from interventions that are likely to shape health and wellbeing. We suggest that this typology can be used to assess the health consequences of adaptation interventions more generally and argue that such forms of evaluation will better support the development of sustainable adaptation planning.

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Multi-dimensional well-being associated with economic dependence on ecosystem services in deltaic social-ecological systems of Bangladesh - Helen Adams; W. Neil Adger; Sate Ahmad; Ali Ahmed; Dilruba Begum; Zoe Matthews; Mohammed Mofizur Rahman; Kristine Nilsen; Georgina Grace Gurney; Peter Kim Streatfield (Regional Environmental Change, 2020)
While the benefits humans gain from ecosystem functions and processes are critical in natural resource-dependent societies with persistent poverty, ecosystem services as a pathway out of poverty remain an elusive goal, contingent on the ecosystem and mediated by social processes. Here, we investigate three emerging dimensions of the ecosystem service-poverty relationship: economic contribution of provisioning ecosystem services to the household livelihood mix, social-ecological systems producing different bundles of ecosystem services and material wealth versus reported life satisfaction. We analyse these relationships in Bangladesh, using data from a bespoke 1586-household survey, stratified by seven social-ecological systems in the delta coastal region. We create poverty lines to ensure comparability with traditional poverty measures that overlook environmental factors and subjective measurements of well-being. We find that any contribution of ecosystem service-based income to the livelihood mix decreases the likelihood of the incidence of poverty, and of individuals reporting dissatisfaction. We find no relationship between the incidence of material poverty and the specific social-ecological systems, from agriculture to fishery-dominated systems. However, the probability of the household head being dissatisfied was significantly associated with social-ecological system. Individuals living in areas dominated by export-oriented shrimp aquaculture reported lower levels of life satisfaction as an element of their perceived well-being. These results highlight the need for social policy on poverty that accounts for the diversity of outcomes across social-ecological systems, including subjective as well as material dimensions of well-being. National poverty reduction that degrades ecosystem services can have negative implications for the subjective well-being of local populations.

Reef Grief: investigating the relationship between place meanings and place change on the Great Barrier Reef, Australia - Nadine Marshall; William Neil Adger; Claudia Benham; Katrina Brown; Matthew I Curnock; Georgina G Gurney; Paul Marshall; Petina L Pert; Lauric Thiault (Sustainability Science, 2019)

Soil salinity, household wealth and food insecurity in tropical deltas: evidence from south-west coast of Bangladesh - Sylvia Szabo; Md. Sarwar Hossain; W. Neil Adger; Zoe Matthews; Sayem Ahmed; Attila N. Lázár; Sate Ahmad (Sustainability Science, 2016)

Climate and security: evidence, emerging risks, and a new agenda - François Gemenne; Jon Barnett; W. Neil Adger; Geoffrey D. Dabelko (Climatic Change, 2014)

Assessment of institutional capacity to adapt to climate change in transboundary river basins - Anita Milman; Lisa Bunclark; Declan Conway; William Neil Adger (Climatic Change, 2013)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

Are there social limits to adaptation to climate change? - W. Neil Adger; Suraje Dessai; Marisa Goulden; Mike Hulme; Irene Lorenzoni; Donald R. Nelson; Lars Otto Naess; Johanna Wolf; Anita Wreford (Climatic Change, 2009)

Implications of Livelihood Dependence on Non-Timber Products in Peruvian Amazonia - Aili Pyhälä; Katrina Brown; W. Neil Adger (Ecosystems, 2006)

Defining and Experiencing Dangerous Climate Change - Suraje Dessai; W. Neil Adger; Mike Hulme; John Turnpenny; Jonathan Köhler; Rachel Warren (Climatic Change, 2004)

Climate Dangers and Atoll Countries - Jon Barnett; W. Neil Adger (Climatic Change, 2003)

Social Vulnerability to Climate Change and the Architecture of Entitlements - W. Neil Adger; P. Mick Kelly (Mitigation and Adaptation Strategies for Global Change, 1999)